Power Sharing in Syria: Lessons from Lebanon's Experience - Stephan Rosiny (German Institute of Global and Area Studies (GIGA), 2013)
In the last two years, the Syrian uprising has turned from a civil protest movement against an authoritarian regime into an outright civil war in which the antagonists affiliations' and identities are increasingly framed in sectarian speech. In summer 2012, various politicians and analysts suggested a power-sharing agreement between regime and opposition representatives as a solution to break the vicious circle of escalating violence. They called it a Syrian Taifh after the 1989 peace accord that ended Lebanon's long-lasting civil war (1975-1990) by dividing power among religious communities. Others rejected the idea of a consociational power-sharing deal outright because they hold it responsible for the continued sectarian pillarization of Lebanese society. Moreover, Syria's experience is said to differ significantly from Lebanon's, making the effective transmittal of the Lebanese model impossible. This paper takes these differing arguments into consideration and investigates whether power sharing could help to deescalate the Syrian conflict and what lessons should be taken from Lebanon's experience. Lebanon shows that consociationalism tends to stabilize - even deepen - social cleavages. Therefore, a Syrian Taif should gradually substitute fixed guarantees of shares of power with centripetal and unitary state institutions. Furthermore, in addition to internal actors, external powers have to be convinced that power sharing may be the only viable option for ending the devastating civil war in Syria and for preventing the further spread of violence into neighboring countries.
Keywords: 300; power sharing; civil war; sectarianism; Syria; Lebanon; Taif